Reduceți termenii asemenea:
a) 9z + 11z - 8 + z =
b) 2.5x + 0.5x - 1.5x + 3.5x - 1.2x =
c) 3.75b - 1.25b + (b - 0.3b) - (0.7b + 0.3b) =
d) 2.7a - (3.8a - 0.3a + 0.5a) + 1.3a =

2
a) 9z + 11z - 8 + z = 21z - 8
b) 2.5x + 0.5x - 1.5x + 3.5x - 1.2x = - 3,2x

Răspunsuri

Cel mai inteligent răspuns!
2014-06-28T12:47:50+03:00
A) 21 z -8
b) x( 2,5 +0,5 -1,5 + 3,5 - 1,2) = 3,8x
c) 2,5b + 0,7 b - b= 2,2 b
d)2,7 a  - 4a + 1,3 a = 0a =0
1 5 1
  • Utilizator Brainly
2014-06-28T15:15:52+03:00
A) 9z + 11z - 8 + z = 0
21z - 8 = 0
21z = 8
z = 21/8
b) 2.5x + 0.5x - 1.5x + 3.5x - 1.2x = 3.8x
c) 3.75b - 1.25b + (b - 0.3b) - (0.7b + 0.3b) = 2.5b+0.7b-1b= 2.2b
d) 
2.7a - (3.8a - 0.3a + 0.5a) + 1.3a = 2.7a - 4a + 1.3a = 0